Gold-decorated magnetic nanoparticles design for hyperthermia applications and as a potential platform for their surface-functionalization - León Félix, L. (2019)
The integration of noble metal and magnetic nanoparticles with controlled structures that can couple various specific effects to the different nanocomposite in multifunctional nanosystems have been found interesting in the field of medicine. In this work, we show synthesis route to prepare small Au nanoparticles of sizes = 3.9 ± 0.2 nm attached to Fe 3 O 4 nanoparticle cores ( = 49.2 ± 3.5 nm) in aqueous medium for potential application as a nano-heater. Remarkably, the resulted Au decorated PEI-Fe 3 O 4 (Au@PEI-Fe 3 O 4 ) nanoparticles are able to retain bulk magnetic moment M S = 82–84 Am 2 /kg Fe3O4 , with the Verwey transition observed at T V = 98 K. In addition, the in vitro cytotoxicity analysis of the nanosystem microglial BV2 cells showed high viability (>97.5%) to concentrate up to 100 µg/mL in comparison to the control samples. In vitro heating experiments on microglial BV2 cells under an ac magnetic field (H 0 = 23.87 kA/m; f = 571 kHz) yielded specific power absorption (SPA) values of SPA = 43 ± 3 and 49 ± 1 μW/cell for PEI-Fe 3 O 4 and Au@PEI-Fe 3 O 4 NPs, respectively. These similar intracellular SPA values imply that functionalization of the magnetic particles with Au did not change the heating efficiency, providing at the same time a more flexible platform for multifunctional functionalization.